Keberhasilan Harga Saham dan Aksi Stock Split - Ramania, Yosepphira Intan Permata; Supramono (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
Stock split is a corporate action taken by a company to increase stock liquidity. There is a phenomenon of companies that failed and succeed after carrying out stock split actions. This study aims to examine the company's financial performance and market performance against the success of the stock price after the stock split. The sample of this study is companies listed on the Indonesia Stock Exchange and conducted a stock split in the period 2018 – 2021, using purposive sampling and obtained 41 companies. For the benefit of hypothesis testing using multiple linear regression analysis techniques. The results of the study that financial performance and market performance had no effect on the success of the stock price after the stock split. The results of this study imply that the stock split has not been able to be used as a signaling instrument about the company's positive prospects.